2002
DOI: 10.1046/j.1471-1842.2002.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of distance learning delivery of health information management and health informatics programmes: a UK perspective

Abstract: The aim of the article is to review evaluations of distance learning programmes in health information management, in order to identify the critical success factors for such programmes and discuss future directions. The emphasis is on the UK experience, based partly on reflections on the experience of one programme at University of Wales Aberystwyth (now over 10 years old), and partly on a policy review conducted for the NHS Information Authority and the NHS Information Policy Unit. The methods are, as far as p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Approaches to continuing professional development that may suit the specific needs of project staff include distance learning, mentoring and action learning sets. Distance learning 5 and mentoring 6 are individual‐centred approaches that require access to suitable courses or to experienced individuals. Where several projects commence at approximately the same time, it may be more appropriate to employ a group‐led process such as action learning.…”
Section: Action Learning Setsmentioning
confidence: 99%
“…Approaches to continuing professional development that may suit the specific needs of project staff include distance learning, mentoring and action learning sets. Distance learning 5 and mentoring 6 are individual‐centred approaches that require access to suitable courses or to experienced individuals. Where several projects commence at approximately the same time, it may be more appropriate to employ a group‐led process such as action learning.…”
Section: Action Learning Setsmentioning
confidence: 99%
“…Similarly, Hersh et al 10 developed the Sharable Content Object Reference Model by linking competencies to the learning objectives and the curriculum of e-leaning courses in medical informatics. Urquhart et al 11 suggested that the integration of workplace learning with the curriculum and assessment methods is critical to the success of distance learning programs in health information management and health informatics.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Zhang 5 suggested that CBL is an effective approach to teaching SAD because students need to be able to develop real-world information systems rather than just obtaining theoretical knowledge. Review of the literature indicated that although some researchers have been conducting research on the use of CBL in health informatics courses, [10][11][12] there has been no research conducted to link competencies to the SAD curriculum and then measured those competencies using a competency diary. Because SAD requires that one has the practical IT skills necessary to analyze and design complex information systems, a CBL approach that emphases the ability to apply knowledge and skills to solving real-world problems should be an effective way to deliver an online SAD course.…”
Section: Introductionmentioning
confidence: 99%
“…Also in 2002, Urquhart and colleagues, in reviewing the aims, objectives and educational philosophies of health information and health informatics programmes, concluded that face‐to‐face interaction fulfils a key role in complementing distance learning. More significantly, they affirmed that a ‘student‐centred approach to curriculum design and delivery is essential’ 7 …”
Section: Health Informatics Education and Trainingmentioning
confidence: 99%